THE TRANSITIONAL EVOLUTION OF IMPRISONMENT PURPOSES - Vorapatr, Thanee (Rangsit Journal of Law and Society, 2022)
The concepts regarding the punishment had been based on the following objectives 1). The punishment as the substitute, 2).The punishment to intimidate, 3).The punishment to preclude the offences, and 4).The punishment to improve. Afterwards, such concepts and practices were developed to become more democratic and humanitarian, expressed in various principles. For instance, the rule of law, legal state, human rights, and human dignity. These have been recognized and implemented in the agreements, the standards, the regulations, and the treaties at the international level. Moreover, the enforcement of the constitutional laws and the specific domestic laws have also been consistent with the above principles. Pursuant to the fact that the theories and the practices regarding the imprisonment have been developed in accordance with the way of the world, the concepts and the practices of the imprisonment were established to serve the following objectives, 1). To allow the offenders to live without committing the offenses and to have the social responsibility in the future 2). To protect the society. Moreover, the purposes of the punishment and the enforcement are beneficially integrated to protect the equilibrium of human life protection, as follows, 1). To allow the offenders to live without committing the offenses and to have the social responsibility in the future, 2). To protect the society, 3). To allow the appropriate revenge, preventing the unlawful revenge, 4). To intimidate, in order to prevent others to follow such actions, and 5). To eliminate the opportunity to commit an offense. Therefore, this study suggests that the policies, the laws, and the practices in relation to the punishment in Thailand should be amended and improved in accordance with the aforementioned new objectives.